2017
DOI: 10.1111/eci.12744
|View full text |Cite
|
Sign up to set email alerts
|

The association between systemic lupus erythematosus and valvular heart disease: an extensive data analysis

Abstract: All VHD are more prevalent among SLE patients when compared to controls. SLE and aPLs are independent risk factor for VHD (OR of 2·46 and 1·7, respectively). Physicians must be aware of such significant association, and routine echocardiography should be considered in SLE patients regardless of their aPL status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 39 publications
0
20
0
Order By: Relevance
“…The validity and reliability of the diagnoses in the registry were found to be high, as shown in our previously published studies. [32][33][34][35] Serum samples were taken and analyzed in SSc-patients by indirect immunofluorescence or enzyme-linked immunosorbent assay to identify SSc-specific autoantibodies during the diagnosis approach or follow-up and were available for the years 2010-2017. These tests were performed as part of the clinical routine and were not research assays.…”
Section: Methodsmentioning
confidence: 99%
“…The validity and reliability of the diagnoses in the registry were found to be high, as shown in our previously published studies. [32][33][34][35] Serum samples were taken and analyzed in SSc-patients by indirect immunofluorescence or enzyme-linked immunosorbent assay to identify SSc-specific autoantibodies during the diagnosis approach or follow-up and were available for the years 2010-2017. These tests were performed as part of the clinical routine and were not research assays.…”
Section: Methodsmentioning
confidence: 99%
“…CHS performs the process of validation by logistic checks (such as comparing diagnoses from various providers) and by direct validation of the diagnoses of treating physicians. The validity of the diagnoses in the registry has been shown to be high [20-24]. …”
Section: Methodsmentioning
confidence: 99%
“…The heart is an example of such an organ, given the high prevalence of cardiovascular disease in SLE of over 50%. [17] Valvular abnormalities are quite prevalent in SLE patients, including aortic valve regurgitation, which was reported to be one of the most common valvular impairments observed. [18] One of the most prevalent cardiac manifestations of SLE is Libman-Sacks endocarditis with 1-4 mm large, verrucous vegetations present on either side of the aortic and mitral valves [19].…”
Section: Systemic Lupus Erythematosus and Antiphospholipid Syndromementioning
confidence: 99%
“…However, this rate rises when renal failure is involved, as it causes more rapid valve deterioration. [17] Moreover, one retrospective analysis concluded that cardiac surgery in SLE confers a high rate of mortality and morbidity, with early and late death reported in 17% and 10% of patients, respectively. The main cause of these deaths was sepsis, with at least one postoperative complication occurring in 63% of cases.…”
Section: Systemic Lupus Erythematosus and Antiphospholipid Syndromementioning
confidence: 99%